Think, play, do : technology, innovation, and organization - Dodgson, Mark, 1957- (Oxford University Press, 2005)
Without innovation, companies die. Managing the innovation process well is important for companies and for nations as a whole. This book shows how the innovation process is changing profoundly, with significant implications for managers and public policy-makers. A new kind of technology, 'innovation technology' is being applied to the innovation process. When used effectively, innovation technology makes the innovation process faster, better and cheaper. The book outlines a new scheme for the innovation process: Think, Play, Do. Innovation requires creating new ideas and thinking about new opt.